Role of Culture Shock as a Mediator of Relationship between Achiever and Challenger Personality to Sojourner Adjustment - Ujam Jaenudin; Irfan Fahmi; Tahrir; Zulmi Ramdani (Universitas Islam Tribakti Lirboyo Kediri, 2022)
Students who continue their education abroad will be vulnerable to stress and other adaptation problems. Success in overcoming new pressures and situations, one of which is determined by the personality characteristics of each person. This research aims to determine the role of culture shock as a mediator of the relationship between the personality of the achiever and the challenger to the sojourner adjustment. Causality quantitative research design is used to answer this goal by involving research respondents, namely Pattani students who are Muslim and are studying in the city of Bandung. Saturated sampling technique was used to obtain the characteristics of the sample in the research so that as many as 225 respondents were involved in filling out the research questionnaire. The data collection method uses a Likert scale with data analysis using the SEM (Structural Equation Model) approach. Structural analysis shows that cultural shock plays an effective and significant role as a mediator variable in the relationship between the personality of the achiever and challenger to the sojourner adjustment.